Asymptotic behaviour of a model of an age-sex-structured population dynamics - Skakauskas, Vladas (Nonlinear Analysis: Modelling and Control, 1998)
This paper deals with a model of an age-sex-structured population consisting of male, single (nonfertilized) female and fertilized female subclasses taking into account random mating of sexes (during the coupling only), and females’ pregnancy. We analyze the special case of this model where death moduli can be decomposed into the sum of two terms: the first depends on age only and represents death by natural causes, while the second is a function of total population and represents environmental effects. For this model the separable solutions are presented and their asymptotic behaviour is demonstrated.